(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article investigates the status of the aphorism as an object of linguistic inquiry and the problem of delimiting it from other stable (fixed) linguistic units. The aim of the study is to identify the linguistically relevant features of the aphorism and to isolate, among them, its differential feature. Definitions found in reference literature, together with aphoristic material drawn from Chinese, Uzbek and Russian, were examined using methods of definitional, componential and distributive analysis. The criteria of essentiality/non-essentiality and necessity/contingency were applied in evaluating the features. As a result of the analysis, ten features of the aphorism were identified and distributed into three groups — differential, essential and accompanying features. It was established that the feature of "separate formation" is neither essential nor necessary for the aphorism, whereas the function of a differential feature is performed by the generalized character of meaning. The results obtained provide a basis for the practice of marking and classifying aphoristic units in dictionaries.